Definitions of midwifery competence: implications for professional learning - Butler, Michelle (2001)
This study explores the nature of competence required to fulfil the role of the midwife, learning to become competent, and professional learning beyond registration. The research was undertaken through a qualitative, case study approach, exploring competence as a phenomenon, as experienced by thirty-nine student midwives as they went through the final stages of pre-registration midwifery education programmes, were assessed to be competent, and took on the role of the midwife. The views of the thirty-nine participants of competence and of their own capability, development and learning, were compared with the views of teachers, assessors, other midwives, and supervisors of midwives, working with participants. Also explored are the characteristics of the expert and the characteristics of good and bad midwives.